Weeds as plant genetic resources for production of nutritious supplementary food in agriculture - S.M. Rezaul Karim; Ahmad Anwar Mohamed Ismail (2012)
A number of weed plants available in Bangladesh have potential uses as food for human and as medicinal purposes, which need to be conserved in a well-managed herb garden. Most of these weeds can be eaten raw as salad, cooked in soup or the seeds and leaves ground and consumed as teas or in porridge. They are high in essential minerals especially in calcium, magnesium, iron, phosphorus, manganese, zinc etc. They are also high in vitamins A, C, D, and K, niacin, thiamin, riboflavin etc. Some of these are useful for the remedy of digestive disorders, reduce cholesterol levels, some are used as antidotes against poisoning from arsenic and mercury. Watercress is a good source of antioxidants and helps in curing breast cancer and the weed can also be grown as trap crop for caterpillars and black aphids. White horehound can be used as natural repellants for grasshoppers. Ash of bracken is high in potassium and can be used in the fields as fertilizer. Research initiatives to study some of these weeds turning them as PGRFAs (Plant Genetic Resources for Food and Agriculture) specifically focusing on their biology, their potential for food production, advanced growing techniques, etc. have been emphasized. Introduction